The use of information and communication technology in teaching and learning operation by academicians at higher education institution - Mokhtar, Rashidah; Jaafar, Nur Huda; Ismail, Zuriati; Abd Rahman, Mazlyda; Azman Ong, Mohd Hanafi; Ramlan, Rohaizan (Penerbit UTHM, 2020)
Teaching and learning (T&L) delivery method is a main focus that every higher education institution needs to consider in their strategic planning. This is to ensure the academicians have clear teaching direction thus will result in more effective and clearer reception of knowledge by the students. T&L techniques have gone through several phases of revolution to be in line with current needs. Table 3.1 shows the comparison of education 1.0 to 4.0 as stated by Harkins (Harkins, 2008). The education revolutions show the changes of teaching and learning style from the teacher-centered learning to student-centered learning which influence the methods and technologies in T&L. Education 1.0 used traditional concept of T&L without being influenced by any technology. In education 2.0, students and academicians have been exposed with the Internet technology in T&L but it is not used widely in teaching and learning delivery method. In the education 3.0 era, the student-centered learning concept has evolved with an emphasis on the concept of constructivism. The constructivism concept encourages students to develop their knowledge from experiences with supported technologies such as Massive Open Online Course (MOOC). This concept also encourages interaction between students and educators and it supports students to share their views with educators’ intervention.